Diagenesis and Provenance of Lati Sandstones in the Berau Area, East Kalimantan Province, based on Petrography Data - Maryanto, Sigit (Geological Agency, 2012)
DOI:Â 10.17014/ijog.v7i3.143This study is focused on the provenance and diagenetic processes affecting the sandstones of Lati Formation cropping out at Berau Area, East Kalimantan Province. Petrographic analysis of twenty-two samples from this formation shows that these sandstones are classified as litharenite, feldspathic litharenite, sublitharenite, feldspathic wacke, and lithic wacke, which are partially calcareous. Preserved diagenetic processes were visible on the petrographic analysis including cementation, replacement, dolomitization, compaction, and dissolution. The provenance of these sandstones is dominated by granitic rocks initiated from tectonic setting of rifted continental margin, transported toward southeast.